N-myc amplification in neuroblastomas: histopathological, DNA ploidy, and clinical variables. - Oppedal, B R (1989)
The association between tumour N-myc amplification, DNA ploidy, and various prognostic factors (patient age, tumour stage at diagnosis, primary site and histopathological differentiation) was studied in 18 children who had neuroblastoma, ganglioneuroblastoma, or ganglioneuroma. Amplification of genomic N-myc was observed in six patients who had been treated with chemotherapy before surgery (one with stage III and five with stage IV). All these tumours were located in the adrenal or upper retroperitoneum; five were neuroblastomas and one was a ganglioneuroblastoma. Three of them were aneuploid and three diploid. The degree of N-myc patients with tumour N-amplification varied from 20 to 1500 copies without relation to ploidy. All patients with tumour N-myc amplification died of their tumour. Amplification was always associated with poor prognosis, independent of tumour cell ploidy. Four patients without such amplification also died: three had diploid tumours, the fourth was aneuploid. It is suggested that genomic N-myc amplification takes place mainly in adrenal and retroperitoneal neuroblastomas and can be a feature of tumours with and without histological signs of differentiation. The precise role of N-myc in the pathogenesis of neuroblastoma remains unclear.